IMPLEMENTASI CSR PT. ANGKASA PURA I BANDARA INTERNASIONAL JUANDA SEBAGAI UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT DITENGAH PANDEMI COVID-19 MELALUI PROGRAM UMKM WANI (Universitas Negeri Surabaya, 2022)
The Covid-19 pandemic that occurred in Indonesia brought up several problems, and one of them is the economic field. CSR as one of the company's obligations has a role in dealing with economic problems due to this pandemic. So does PT. Angkasa Pura I Juanda International Airport did in planning a CSR program based on current conditions. This study aims to explore how the implementation of Angkasa Pura Juanda's CSR as a form of its efforts to empower the society's economy in the middle of the Covid-19 pandemic. The data of this study is collected through in-depth interviews with six informants, and two CSR staff of PT. Angkasa Pura I Juanda International Airport and the rest of the informants are people of the company's miter. The results of this study show that the UMKM Wani program is implemented in the form of disbursement of funds, training, promotion, certification and stimulus. The program has benefits for the assisted MSMEs. Because of this, the old company’s miter trust the company so they give recommendation to the other MSMEs, and become new company’s miter. This affects the good image of the company that arises because of the trust of the company’s miter.